Evaluasi Program Sekolah Adiwiyata di Sekolah Dasar Muhammadiyah Bantul Kota - Anindya Chasti Pelita; Hendro Widodo (Universitas Negeri Malang, 2020)
This study aims to evaluate and describe the supporting and inhibiting factors in the implementation of the Adiwiyata program at Muhammadiyah Bantul City Elementary School. This type of research is evaluative research with the CIPP model. Collecting data through observation, documentation, and interviews. The results showed that the context component contained environmental protection and management efforts, the input component included the budget used, the process component including the maintenance of facilities and infrastructure needed to be improved, and the product component showed that there were quite a several academic and non-academic products produced. The supporting factors for the implementation of the Adiwiyata program are supporting human resources and infrastructure, while the inhibiting factor is the lack of environmental sensitivity and knowledge of the school community. Penelitian ini bertujuan untuk mengevaluasi dan mendeskripsikan faktor pendukung dan penghambat dalam pelaksanaan program Adiwiyata di Sekolah Dasar Muhammadiyah Bantul Kota. Jenis penelitian ini penelitian evaluatif model CIPP. Pengumpulan data melalui observasi, dokumentasi, dan wawancara. Hasil penelitian menunjukkan komponen context memuat upaya perlindungan dan pengelolaan lingkungan hidup, komponen input mencakup anggaran yang digunakan, komponen process mencakup pemeliharaan sarana dan prasarana perlu ditingkatan, serta komponen product menunjukkan cukup banyak produk yang dihasilkan akademik dan non-akademik. Faktor pendukung pelaksanaan program Adiwiyata adalah dukungan sumber daya manusia dan sarana prasarana, sedangkan faktor penghambat adalah kurangnya kepekaan dan pengetahuan lingkungan hidup dari warga sekolah.